Integrating Assessment for Learning in the ESL/EFL Writing Classroom - Yogyantoro Yogyantoro; Noer Doddy Irmawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Assessment for learning (AfL) is a concept that falls into a new category in ESL/EFL writing. At AfL, learning is an end in itself, and assessment acts as a means to an end. However, the emphasis on the assessment of the AfL concept raises several suggestions, in implementing AfL, teachers are required to be able to integrate teaching, learning and assessment at once rather than just focusing exclusively on how to assess students' writing themselves. This article aims to discuss the key concepts AfL refers to writing and provide easy-to-implement suggestions to assist teachers in ESL/EFL writing  and practicing AfL in the classroom.